(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In this article described an experiment about the feeding the russian sturgeon by home man-made foods with various additions. Given estimation of the physiological condition of young russian sturgeons arcading to fish-breeding and biological parameters and biochemical parameters of blood. By virtue of got database found the food with addition, which more balanced and nutritious go the sturgeon fishes bred in basius.